Partisipasi Masyarakat Terhadap Pengelolaan Sampah Di Kelurahan Sukorejo Kecamatan Gunungpati Kota Semarang Tahun 2020 - Nugroho, A.D. Cahyo; Sujatmiko, Amin; Waskito, Waskito (Indonesian Journal of Geography Education; Vol 1 No 2 (2020): Indonesian Journal of Geography Education, 2021)
One problem that is faced by society modern now this is rubbish as a result of blasting the population and changes in patterns of consumption society that increasingly the day increasingly rising . The issue of garbage is difficult to look for a solution that is effective that relate to the means of participation of the community itself as a manufacturer of main rubbish and infrastructure are lacking adequate also awareness of the public who have not fully exist about cleanliness especially garbage . One of the program handling the problem of waste that is not separated from the support of the government center and government area of the program handling the problem of waste through the 3R namely REDUSE : reducing the use of products that will produce garbage . Reuse : using the reset , sell or donate items that still can be used . Recycle : modify the object that was not helpful , be helpful . Participation of the community plays a role important in the implementation of the 3R program so that the problem of garbage can be resolved with a more comprehensive and supported by a system that both are regulated by the government . To this it takes awareness and participation of the community to preserve the environment to be able to realize the environment that is clean , healthy , and beautiful . Based on the results of the study recommended as follows : (1) government officials rt / rw and managers to educate the community in a planned and measured on the management of garbage that is true . (2) the government regulate and provide intensive and disincentive to motivate people . (3) government , caretaker rt / rw and managers making mechanisms and determine people to monitor and evaluate the management of litter -based society . (4) the government provides waste management facilities and infrastructure . (5) managers and administrators of rt / rw look for management cadre strategies .